On a new transmuted three-parameter lindley distribution and its applications - Xi, Yuhang; Lu, Hezhi; Liang, Fei (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this paper, a new transmuted three-parameter Lindley distribution (TTHPLD) is established using the transmutation map method, which includes the Lindley distribution, two-parameter Lindley distribution, transmuted two-parameter Lindley distribution and three-parameter Lindley distribution as special cases. The statistical properties of the TTHPLD model, which are based on moments, order statistics, hazard rate functions, reliability functions, and Renyi entropy, have been studied. Moreover, the maximum likelihood estimators (MLEs) of the TTHPLD are obtained via differential evolution algorithms, and a simulation study is conducted to evaluate the consistency of the MLEs. Finally, the proposed distribution is applied to a real dataset and compared with other well-known models.